Identitas-Identitas Teologis Kristen Protestan Indonesia Pasca Orde Baru: Sebuah Pemetaan Awal - Julianus Mojau (Faculty of Theology Duta Wacana Christian University, 2017)
Abstract Protestant Christianity in Indonesia cannot be inconsistant with the general principle of Protestantism worldwide: sola scriptura. That is why biblical identity is one of the identity markers of Protestant Christians in Indonesia. Also, it is impossible to understand the identity of Protestant Christianity in Indonesia, apart from christology as a marker of the identity in appreciating the second general principle of Protestantism: sola gratia. The unity of God as the trinity has also become another marker of identity. In the past these three identity markers are often seen as distinctive identities to